Detection of Recurrent Bladder Cancer: NMP22 Test or Urine Cytology? - Hosseini, Jalil; Golshan, Ali Reza; Mazloomfard, Mohammad Mohsen; Mehrsai, Abdolrasoul; Zargar, Mohammad Ali; Ayati, Mohsen; Shakeri, Saeed; Jasemi, Majid; Kabiri, Mahmoud (Urology Journal, 2012)
Purpose: To assess the accuracy of voided urine cytology versus urinary nuclear matrix protein 22 (NMP22) qualitative assay in the diagnosis of various grades and stages of recurrent bladder transitional cell carcinoma (TCC). Materials and Methods: From July 2007 to February 2009, all patients with history of superficial bladder TCC were included in this multi-center study. Each patient provided three serial voided urine samples for cytologic examination and one sample for the NMP22 qualitative assay prior to urethrocystoscopy. The sensitivity and specificity of urine cytology and the NMP22 test were determined. Results: The sensitivities of the NMP22 test and cytology for detection of recurrence were 78.8% and 44.2%, respectively (P = .001), while the specificities were 69.6% and 83.7%, respectively (P = .019). The NMP22 test showed significantly higher sensitivity than cytology in detecting recurrences in low-risk and intermediate-risk groups. Conclusion: The NMP22 assay could be used for detection of superficial bladder cancer, especially in low- and intermediate-risk groups; however, the value of the test is limited by its low specificity.